Developments in Buddhist Studies - Lopez, Donald S., Jr. (Canadian Journal of Buddhist Studies, 2016)
This report summarizes the proceedings of "Buddhist Studies Today," a symposium convened at the University of British Columbia and sponsored by the American Council of Learned Societies with support from The Robert H. N. Ho Family Foundation. It was a three-day symposium to celebrate the first Dissertation Fellows of The Robert H. N. Ho Family Foundation Program in Buddhist Studies and to reflect on their work.,